Prophylactic and Therapeutic Use of Strontium Ranelate Reduces the Progression of Experimental Osteoarthritis - Rodrigues, Thiago A.; de Oliveira Freire, Abner; Carvalho, Heetor C. O.; Silva, Gyl E. B.; Vasconcelos, José W.; Guerra, Rosane N. M.; de Sousa Cartágenes, Maria do Socorro; Garcia, João B. S. (Frontiers in Pharmacology, 2018)
Introduction: Strontium ranelate (SrRan) has the potential to interfere in the progression of osteoarthritis (OA), multifactorial disease associated with mechanical problems and articular inflammatory changes. Objectives: This study aimed to test the effects of prophylactic and therapeutic use of SrRan on clinical parameters of pain, the inflammatory process, and degradation of the articular cartilage. Methods: This was an experimental study, using a model of knee OA induced by intra-articular injection of monoiodoacetate. Thirty Wistar rats were divided into five groups and treated as indicated: control, without intervention; prophylactic, received SrRan at a daily oral dose of 250 mg/kg for 28 days before OA induction; SrRan treatments, administered 250 or 500 mg/kg/day for 28 days after the induction; and model control, received saline solution after the induction. Behavioral tests (joint incapacity, mechanical hyperalgesia, tactile sensitivity, and forced ambulation), histological evaluation of articular cartilage, and determination of inflammatory cytokines in the synovial fluid (interleukin [IL]-6, IL-10, tumor necrosis factor [TNF]-α, and interferon [INF]-γ) were performed. Results: Both prophylactic and therapeutic treatments improved the articular discomfort. A prophylactic dose of 500 mg/kg/day also improved mechanical hyperalgesia and the same dose was beneficial on tactile sensitivity. SrRan did not improve ambulation. Levels of IL-6, IL-10, TNF-α, and IFN-γ in SrRan-treated groups with OA were not significantly different compared with those in the normal control animals. The histopathological evaluation showed less articular damage in the SrRan-treated and control groups compared to the saline-treated group. Conclusions: The prophylactic and therapeutic administration of SrRan was associated with improved behavioral patterns of pain, especially joint discomfort. SrRan administration mitigated histological changes in the articular cartilage and reduced the inflammatory process, which beneficially reduced the progression of OA in the experimental model studied. Keywords: strontium ranelate; osteoarthritis; pain; treatment; inflammation.